DESAIN APLIKASI IDENTIFIKASI GAYA BELAJAR SISWA SEKOLAH DASAR MENGGUNAKAN WEB MOBILE - Anggraeni, Leni; Khatomi, Khatomi; Trisnawati, Trisnawati (STIT AL MULTAZAM, 2022)
In general, every child or student has a different learning style. Educators or teachers should first know the ways and learning styles of their students so that they are able to choose the right teaching method so that the information and material presented can be well absorbed by students. A student must also know his own style and way of learning and be able to choose a method or way of learning that is good and in accordance with his own character. Students will learn if the material presented is interesting and they consider the material important. By applying the Research and Development (RD) method with the ADDIE approach, implementation with limited trials to find out the shortcomings and inputs about the application that has been made, namely the application of an expert system to identify student learning styles using a mobile web. Therefore, making this application aims to create an expert system to identify student learning styles that aim to get good, effective, and efficient learning outcomes and are right on target in a learning cycle as the object is students or students, and as the implementation is the teaching teacher